The patient-reported outcome measure for older people living with frailty receiving acute care (PROM-OPAC): field-testing and validation - James D. van Oppen; Simon P. Conroy; Jagruti Lalseta; Nicola Mackintosh; Peter Riley; Vivien Richardson; Jose M. Valderas; Timothy J. Coats (Journal of Patient-Reported Outcomes)
Abstract Background Current acute healthcare service metrics are not meaningful for older people living with frailty. Healthcare knowledge, situational security, and physical and psychosocial function are important outcomes typically not collected. The use of patient-reported outcome measures (PROMs) could support these assessments. Existing instruments are not comprehensive as they typically consider function, while older people with frailty also value enablement (self-determination and security in health and healthcare). This study field-tested and validated a PROM for older people with frailty receiving acute care (PROM-OPAC) to measure enablement. Methods People aged 65+ with Clinical Frailty Scale 5–8 were recruited within seventy-two hours of an emergency attendance. Iterations of the novel instrument were administered over three stages: (1) preliminary field-testing for reliability (response distribution and internal consistency) and structure (exploratory factor analysis, EFA); (2) intermediate field-testing of an improved instrument for reliability and structure; (3) final draft validation assessing reliability, structure (confirmatory factor analysis, CFA), and construct validity based on a priori hypotheses. Feasibility was appraised throughout using data completeness and response rates and times. Results 241 people participated. Three items of a preliminary seven-item measure had poor response distribution or loading and were accordingly improved. The intermediate instrument had interpretability issues and three items required further improvement. The final eight-item draft had acceptable reliability (Cronbach’s alpha: 0.71), structure (two factors for self-determination and security; RMSEA: 0.065; TLI: 0.917; CFI: 0.944), and construct validity (lower scores from respondents waiting longer and requiring admission). Feasibility was promising (response rate 39%; 98% responses complete; median completion time 11 (IQR: 12) minutes). Conclusions Administration of the PROM-OPAC appeared feasible and the instrument had acceptable psychometric properties. Further evaluation is required to assess generalisability.